2022
DOI: 10.1017/s0954579421001309
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between parenting and environmental sensitivity in the prediction of children’s externalizing and internalizing behaviors during COVID-19

Abstract: The interplay of parenting and environmental sensitivity on children’s behavioral adjustment during, and immediately after, the COVID-19 lockdown restrictions was investigated in two longitudinal studies involving Italian preschoolers (Study 1, N = 72; 43% girls, Myears = 3.82(1.38)) and primary school children (Study 2, N = 94; 55% girls, Myears = 9.08(0.56)). Data were collected before and during the first-wave lockdown (Studies 1 and 2) and one month later (Study 1). Parental stress and parent–child closene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 72 publications
6
46
0
1
Order By: Relevance
“…Our results showed a signi cant increase of dysregulation levels from T1 to T2 followed by a decrease trend from T2 to T3. As noted in the tools section, the dysregulation pro le is composed by internalizing and externalizing problems; a large amount of studies has now demonstrated that the pandemic has caused a strong increase in these di culties in children, especially in offspring as young as in our sample (see for example: [48,49]). Emotion regulation in preschoolers is crucial for positive outcomes in later life therefore this result rises serious concerns about possible negative consequences in the development of an entire generation of children (as every child in the world has been exposed, more or less directly, to the effects of the pandemic).…”
Section: Discussionmentioning
confidence: 98%
“…Our results showed a signi cant increase of dysregulation levels from T1 to T2 followed by a decrease trend from T2 to T3. As noted in the tools section, the dysregulation pro le is composed by internalizing and externalizing problems; a large amount of studies has now demonstrated that the pandemic has caused a strong increase in these di culties in children, especially in offspring as young as in our sample (see for example: [48,49]). Emotion regulation in preschoolers is crucial for positive outcomes in later life therefore this result rises serious concerns about possible negative consequences in the development of an entire generation of children (as every child in the world has been exposed, more or less directly, to the effects of the pandemic).…”
Section: Discussionmentioning
confidence: 98%
“…turn, influenced children's well-being and adjustment (Lionetti et al, 2022;Spinelli et al, 2020). The main aim of the present study was to investigate how and to what extend the activities performed at home during the lockdown by children and adolescents were related to their emotional and behavioural well-being.…”
mentioning
confidence: 92%
“…Activities conducted at home were more limited and mostly carried out alone, or with the parent. These substantial changes in daily routines and activities had an impact on parents, and this, in turn, influenced children's well‐being and adjustment (Lionetti et al, 2022 ; Spinelli et al, 2020 ). The main aim of the present study was to investigate how and to what extend the activities performed at home during the lockdown by children and adolescents were related to their emotional and behavioural well‐being.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this last process, findings resulting from longitudinal studies are still scarce. Italian children showed an increase in externalizing and internalizing behaviors when the quality of the parent–child relationship was low in closeness and when parents presented high levels of stress (Lionetti et al, 2022). Parent flexibility was associated with greater family cohesion, lower family discord and greater use of constructive parenting strategies during the COVID-19 lockdown, which in turn predicted lower child distress (Daks et al, 2020).…”
mentioning
confidence: 99%